Integrating Web 2.0. Tools “Blog” and “Wiki” into Academic Writing Programme at University - Jasionavičienė, Sandra (Pedagogika, 2013)
This article presents a new approach towards teaching writing in English. The 21st century learners communicate basically in writing – writing text messages, instant messages, e-mail messages, etc. Every person wants to become and to be an accomplished writer, engaged learner and active participant in the present-day digital and interconnected world. Therefore, educators around the globe started talking about teaching digital writing and the need to change the teaching methods to meet the needs of their learners who are now called digital natives and to reduce the digital divide between teachers and students. That is why, the Web which provides a read-write environment nowadays can be used in the teaching-learning process, especially teaching writing skills. Such Web 2.0 tools as blogs and wikis are seen as providing a great learning space, motivating learners to write and successfully develop their digital writing skills. Besides, these tools provide them with real-life experience, intercultural communication, full participation and interaction not only with the teacher but with other students as well. This way students learn collaboratively which is very important if they want to learn to communicate in the present-day world.